VTA dopamine neuron plasticity – the unusual suspects. (1st November 2016) - Xin, Wendy; Edwards, Nicholas; Bonci, Antonello
Abstract: Dopamine neurons in the ventral tegmental area (VTA) are involved in a variety of physiological and pathological conditions, ranging from motivated behaviours to substance use disorders. While many studies have shown that these neurons can express plasticity at excitatory and inhibitory synapses, little is known about how inhibitory inputs and glial activity shape the output of DA neurons and therefore, merit greater discussion. In this review, we will attempt to fill in a bit more of the puzzle, with a focus on inhibitory transmission and astrocyte function. We summarize the findings within the VTA as well as observations made in other brain regions that have important implications for plasticity in general and should be considered in the context of DA neuron plasticity. Abstract : Ventral tegmental area (VTA) dopamine neurons are critical for reward related behaviours and display many forms of plasticity. Previous studies have focused on the regulation and expression of plasticity at excitatory inputs, but changes can also occur at inhibitory inputs and in nearby astrocytes, which may have important consequences for dopamine neuron output. The following review will examine a few ways in which inhibitory inputs and astrocytes can undergo plasticity, and consequently, shape VTA dopamine neuron transmission.